Nutrient availability induces community shifts in seagrass meadows grazed by turtles - Isis Gabriela Martínez López; Marloes van Den Akker; Liene Walk; Marieke M. van Katwijk; Tjisse van Der Heide; Brigitta I. van Tussenbroek (PeerJ, 2019)
In the Caribbean, green turtles graze seagrass meadows dominated by Thalassia testudinum through rotational grazing, resulting in the creation of grazed and recovering (abandoned) patches surrounded by ungrazed seagrasses. We evaluated the seagrass community and its environment along a turtle grazing gradient; with the duration of (simulated) grazing as a proxy for the level of grazing pressure. The grazing levels consisted of Short-term (4 months clipping), Medium-term (8 months clipping), Long-term grazing (8 months of clipping in previously grazed areas), 8-months recovery of previously grazed patches, and ungrazed or unclipped patches as controls. We measured biomass and density of the seagrasses and rhizophytic algae, and changes in sediment parameters. Medium- and Long-term grazing promoted a shift in community species composition. At increasing grazing pressure, the total biomass of T. testudinum declined, whereas that of early-successional increased. Ammonium concentrations were highest in the patches of Medium-term (9.2 + 0.8 μM) and Long-term grazing levels (11.0 + 2.2 μM) and were lowest in the control areas (4.6 + 1.5 μM). T. testudinum is a late-successional species that maintains sediment nutrient concentrations at levels below the requirements of early-successional species when dominant. When the abundance of this species declines due to grazing, these resources become available, likely driving a shift in community composition toward a higher abundance of early-successional species.